Existence and uniqueness of solutions to initial boundary value problem for the higher order Boussinesq equation. (June 2019) - Oruc, Goksu; Muslu, Gulcin M.
Abstract: This paper studies the initial and boundary value problem for the higher order Boussinesq equation. The existence of a local and global solution are proved. The sufficient conditions for finite time blow-up solutions are provided by using the concavity method.